Vegetative Propagation Techniques of Oxytenanthera Abyssinica in Benshangul Gumuz Region, Western Ethiopia (International Journal of Scientific Research and Management (IJSRM), 2020)
Bamboo is a fast-growing woody perennial and grass species, has a unique feature and quality. It has a high potential for socio-economic development and for environmental improvement. The study was conducted in Benshangul Gumuz Regional state, which lowland bamboo highly dominated area. This study aims to identify the best vegetative propagation techniques for Oxytenanthera abyssinica species. Randomized complete block design with three replications was used. The propagation materials were offset, rhizome without node, and rhizome with two-node and whole culm. Totally, 108 planting materials were planted. Nine planting materials were used in each plot level. The survival rate, newly sprouted shoots; their height and root collar increment data were collected. There was a significant difference in number of newly sprouted shoots between the propagation techniques. Higher numbers of sprouted shoots and survival rates were recorded in offset and rhizome with two nodes than rhizome without node and whole culm propagation techniques. While there was a significant difference between the mean shoot height of propagation techniques. In addition, there was no significant difference in root collar diameter between propagation techniques. The finding suggests that rhizome with two-node propagation techniques are appropriate for large and small scale plantation of Oxytenanthera abyssinica.